Fim iminente de um bioma? O avanço das queimadas no Pantanal brasileiro em um cenário de crise climática global - Silva, Amanda Teles da (Universidade Federal de São Carlos, 2025)
The Pantanal has been subjected to increasing anthropogenic pressures, further exacerbated by extreme events driven by human activity. Since 2020, the occurrence of severe and recurrent fires has heightened concerns regarding environmental impacts and the implications for the conservation of the biome. This study aimed to analyze, based on the available literature, the context and effects of wildfires in the Brazilian Pantanal within a scenario of global climate crisis, identifying their main consequences and the future prospects for conservation.The study was conducted through a bibliographic review encompassing scientific articles, technical reports, official documents, and governmental and academic databases. The results indicate that the combination of more severe droughts, climate change, land-use transformations, and the expansion of human activities has contributed to the increased frequency and intensity of fires, thereby compromising the ecological resilience of the biome. Among the observed impacts, biodiversity loss, habitat degradation, and the reduction of flooded areas stand out.Thus, it is understood that the existing response mechanisms remain insufficient in the face of the magnitude of contemporary pressures, making the implementation of integrated public policies and evidence-based management strategies essential to ensure the conservation and ecological integrity of the Pantanal in the coming decades.
Imminent end of a biome? The advance of wildfires in the Brazilian Pantanal in a scenario of global climate crisis
Keywords: Mudanças climáticas; Pantanal brasileiro; Resiliência ecológica; Dinâmica do fogo; Climate change; Brazilian Pantanal; Ecological resilience; Wildfire dynamics; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; 15. Vida Terrestre